1986
DOI: 10.1007/bf00441738
|View full text |Cite
|
Sign up to set email alerts
|

Decreased bone density in severely handicapped children and adults, with reference to the influence of limited mobility and anticonvulsant medication

Abstract: Bone density and related biochemical parameters were investigated in institutionalised children and adults with severe handicaps, who were classified according to the degree of limited mobility (group 1, bed-ridden; group 2, capable of crawling; group 3, capable of walking) and according to whether or not they were receiving anticonvulsants. As determined by microdensitometric analysis of radiograms of the second metacarpal bone, bone width (D), bone pattern area (sigma GS) and bone salt density (sigma GS/D) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…25 It has been reported that the development of bone mass in patients with pediatric SCI never reaches normal levels, which exposes these patients to fractures. 1,36 In the present study the BMD in the lumbar spine reached the level of the general reference population, which shows that at least the mineralisation of central bone returns to normal levels in adolescents with pediatric SCI after initial phases of SCI. The amount of bone mineral loss at hip level was shown to remain at alarmingly low values.…”
Section: Discussionsupporting
confidence: 66%
“…25 It has been reported that the development of bone mass in patients with pediatric SCI never reaches normal levels, which exposes these patients to fractures. 1,36 In the present study the BMD in the lumbar spine reached the level of the general reference population, which shows that at least the mineralisation of central bone returns to normal levels in adolescents with pediatric SCI after initial phases of SCI. The amount of bone mineral loss at hip level was shown to remain at alarmingly low values.…”
Section: Discussionsupporting
confidence: 66%
“…In the present study three of the participants with fractures had sustained their spinal cord injury in childhood when the bone mass was not fully developed and thus never reached a normal level (Nishiyama et al, 1986).…”
Section: Discussionmentioning
confidence: 69%
“…In a series of 118 Japanese children and adults with severe disabilities, Nishiyama and coworkers found that bone density, as assessed by metacarpal bone density, was lower in non-ambulatory patients compared with those who could walk or crawl. Serum 25-OH vitamin D levels were lower in those receiving anticonvulsants; however, most were receiving either phenobarbital or diphenylhydantoin (Nishiyama et al 1986). Two agents, phenobarbital and diphenylhydantoin, have been specifically linked to the effect on serum 25-OH vitamin D by stimulation of the P450 mixed oxidase pathways, thereby metabolizing 25-OH vitamin D to more polar metabolites (Hahn et al 1975).…”
Section: Discussionmentioning
confidence: 99%